Beyond the “Conflict” Paradigm: Western-Muslim Interactions and Intersections (American Journal of Islam and Society, 2016)
Western-Muslim relations have experienced long periods of peaceful coexistence,fruitful co-operation, and close interactions that have enriched both civilizations.And yet an alien observer of our mainstream media could be forgivenfor concluding that “Islam” and the “West” can never co-exist in peace becausethey seem to have nothing in common. In fact, the intermittent violence interruptingthese long peaceful interactions – from the Crusades to the “War onTerror” – has constituted the core of most mainstream media coverage and“scholarship” purporting to “study” and “explain” these relations.In a zero-sum power game, these dominant frameworks emphasize thatsuch a “clash” is inevitable. Samuel Huntington’s “Clash of Civilizations”theory has become the best known articulation and deployment of “conflict”as an “explanatory” framework for understanding current and past Muslim-West interactions. Simply put, existential, cultural, and religious chasmshave put the Muslim world on a collision course with the western world, aproblem that is most exacerbated by the presence of “Islam” and Muslimcommunities in western societies (Huntington, 1993).1 His thesis appearsto ignore each civilization’s internal diversity and pluralism and to be willfullyoblivious to the inter- and intra-civilizational interactions and centuriesoldco-existence, as Edward Said argued in his rebuttal: “Clash of Ignorance”(2001). Beyond the broadest generalizations, after all, what do “Islam” and the“West” mean? How long can we afford to “ignore” the “porousness” and “ambiguity”of their geographical and cultural borders? Is “conflict” between thesetwo realms inevitable? How about the centuries-old dialogue between thesecivilizations, the “Self” and the “Other”? How can researchers and intellectualsdeploy their inter-disciplinary insights and scholarship to address both thereal and the perceived civilizational “chasms”?These questions constitute the overarching themes of some very importantscholarship published in three recent books: Engaging the Other: Public Policyand Western-Muslim Intersections, edited by Karim H. Karim and MahmoudEid; Re-Imagining the Other: Culture, Media, and Western-Muslim Intersections,edited by Mahmoud Eid and Karim H. Karim; and the Routledge Handbookof Islam in the West, edited by Roberto Tottoli. With rich methodologicalapproaches, broad theoretical lenses, and diverse topics, these three books offera unique platform to build both a holistic and nuanced understanding of thecontingencies and intricacies surrounding “Islam” and the “West.” ...